Estar no campo: Processo, Narratividade e Descoberta nos Trabalhos de Gravação de Campo de Thelmo Cristovam e Alexandre Fenerich - Dantas, Paulo (São Paulo, Brazil EDUSP, 2024)
The primary goal with the elaboration of the present text consists of discussing aspects of the process and creative approach of Brazilian artists Thelmo Cristovam and Alexandre Fenerich, with the aim of better understanding their artistic work involving the use of field recordings. Departing from a free reflection regarding the idea of presence in field recordings, developed around texts by Mark Peter Wright, Salomé Voegelin, Tullis Rennie and Isobel Anderson, there follows an analysis and elaborations on excerpts of original interviews and conversations with Cristovam and Fenerich, taking into account their particular narratives regarding the process of creation of such works as Duas Estórias Domésticas Colapsadas and Coleção Peripatética de Sons. This approach reveals uses of field recordings particular to these authors: Cristovam is very much aware of his presence in his recordings, even in those that are characterised by the absence of any sound of an anthropic origin. And Fenerich seems to have found a method in the wandering: there are not, necessarily, projects that are already conceived and that determine a systematic in his outings with the aim of recording. These projects could be discovered during or even after the act of recording.
FRIS
1
Keywords: Music, Thought and Technology